The Tabi Boots Phenomenon. Exploring the Impact of Signature Products on a Brand: A Case Study of Maison Margiela - Angowska, Paulina (Fenomen butów Tabi. Badanie wpływu kultowych produktów na markę na przykładzie Maison Margiela, 2025)
Some fashion products go beyond their functional purpose and become cultural symbols. In the luxury fashion industry, iconic items can significantly impact a brand. This study aims to discover how companies can benefit from signature products and implement them in their overall branding and marketing strategies. It specifically focuses on the Tabi Boot by Maison Margiela, a unique item that has gained increased media attention in recent years. The analysis of branding concepts and the various case studies on iconic products revealed especially a gap in the research on Tabi boots. The main research problem focuses on how consumer perceptions and what behaviours can be observed in regard to iconic products with a focus on Maison Margiela and Tabi boots. This study uses a quantitative method to collect data using a CAWI questionnaire. The findings present valuable insights about the impact that iconic products can have on branding and marketing strategies.
Quote as: Angowska, P. (2025). The Tabi Boots Phenomenon. Exploring the Impact of Signature Products on a Brand: A Case Study of Maison Margiela. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 9-22). Publishing House of Wroclaw University of Economics and Business.
Keywords: Maison Margiela; Tabi Boots; iconic product; luxury fashion; luxury fashion branding; buty Tabi; kultowy produkt; moda luksusowa; strategia marki